(untitled) (The Review of Diabetic Studies, 2025)
Emergency service providers (ESPs) in Middle Eastern countries operate in one of the world’s most extreme climatic environments, where prolonged summer heat and rising humidity intensify the psychological and physiological demands of emergency response work. This review synthesizes current evidence on the relationship between extreme seasonal heat and psychological stress among ESPs, including paramedics, emergency medical technicians, firefighters, and rapid-response personnel. A systematic search of major databases identified studies published between 2010 and 2025, focusing on heat exposure, mental health outcomes, cognitive performance, and occupational strain within Gulf settings. Findings demonstrate that sustained summer temperatures exceeding human thermoregulatory thresholds significantly heighten acute stress, irritability, anxiety, cognitive fatigue, emotional exhaustion, and trauma-related symptoms. Heat acts as both a direct physiological stressor and an intensifier of existing occupational pressures, contributing to burnout, reduced decision-making accuracy, and increased error risk. Environmental factors, such as humidity spikes, radiant heat, sandstorms, and organizational issues including staffing shortages, inadequate cooling systems, and limited mental health support further compound psychological vulnerability. While individual coping, team cohesion, cultural resilience, and leadership support provide protective effects, institutional interventions remain inconsistently applied across the region. Evidence gaps persist due to underreporting, limited region-specific empirical data, inconsistent heat indices, and minimal research involving female and expatriate responders. The review highlights the urgent need for summer-specific operational protocols, improved cooling technologies, AI-driven heat monitoring, and standardized mental health frameworks. Strengthening resilience and policy infrastructures is essential to safeguard ESP wellbeing as climate change continues to intensify extreme heat conditions in the Middle East.